Análisis de sostenibilidad y competitividad de las empresas de transporte y operación turística del cantón Latacunga, provincia de Cotopaxi. - Calvache Villacrés, Eduardo Javier (2023)
The sustainability and competitiveness analysis 12 transport and tourist operation enterprises from Latacunga canton, Cotopaxi province, they registered in the national tourism cadastre. The research type is cross-sectional and relational scope, it is based on the quantitative approach, due to use several statistical and descriptive methods, which helped to assess the two variables. The used technique collects the data from the enterprises was the survey. For assessing the sustainability variable, it was used the InnovaRSE methodology, it is one that plans to implement corporate social responsibility within enterprises, which has a questionnaire 30 questions addressed to three dimensions: economic, environmental and social, giving as a result an index of 2.83, finding in the areas range for improvement and in planning phase. It was used the BID (Inter-American Development Bank) methodology, the aim is the identification existing problems and strengths in the assessed establishments; for measuring the competitiveness variable, it was used an instrument 103 questions, they addressed to eight areas classified as: strategic planning, value chain, quality assurance, merchandising, accounting and finance, human talent, environmental management and information systems; got index is 25.48%, being in a range 21% to 40%, indicating that it has low competitiveness. Once, it was got the indices, it was performed Spearman's statistical correlation test, where the sustainability correlation coefficient results have a value 1,000, by demonstrating, which the variable is correlated with itself. On the other hand, the competitiveness coefficient is 0.200, indicating, which it has no correlation with the sustainability variable, summarizing, the value both variables is greater than 0.05, what determines, which the correlation is not strong or significant, therefore that enterprises are not stable, because their practices do not involve sustainability or competitiveness, which was made a FODA analysis, using the EFI and EFE matrix, getting a total 16 strategies that will help enterprises improve sustainably and competitive within the tourism market, generating more job opportunities and profitability in the short and long term.